2003
DOI: 10.1002/joc.901
|View full text |Cite
|
Sign up to set email alerts
|

Responses of China's summer monsoon climate to snow anomaly over the Tibetan Plateau

Abstract: The climatological features of the winter snow depth over the Tibetan Plateau and the summer precipitation in China are diagnosed using datasets obtained from 78 snow observation stations and 160 rainfall stations during 1957 to 1998. The climatic effects of the snow anomaly over the Tibetan Plateau on the regional summer monsoon climate in China are diagnosed and numerically simulated by use of a regional climate model (RegCM2). The singular value decomposition technique is adopted to diagnose the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
78
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(79 citation statements)
references
References 13 publications
1
78
0
Order By: Relevance
“…A similar correlative field in spring is also found, but for the first SVD, which accounts for 40.46% of the total squared variance and has a correlation coefficient of 0.96 (Figure 8(c), (d)). Similar results have been also indicated by some previous investigators (NCC, 1998;Chen and Wu, 2000;Qian et al, 2003;Zhang et al, 2004;Peng et al, 2005). National Climate Center (NCC, 1998) of China has further found that for winter and spring of more snow over the TP, the large-scale 500 hPa height pattern of '+ − +' meridional correlation mode prevails over East Asia in summer, which is characterized by significant positive correlation at high latitudes (in general, frequent development of blocking situation), negative correlation at mid-latitudes (low pressure disturbances frequently develop over the middle and lower basins of the Yangtze River) and significant positive correlation at lower latitudes (stronger subtropical high over the West Pacific with farther southern position than normal, i.e.…”
Section: Datasupporting
confidence: 90%
See 1 more Smart Citation
“…A similar correlative field in spring is also found, but for the first SVD, which accounts for 40.46% of the total squared variance and has a correlation coefficient of 0.96 (Figure 8(c), (d)). Similar results have been also indicated by some previous investigators (NCC, 1998;Chen and Wu, 2000;Qian et al, 2003;Zhang et al, 2004;Peng et al, 2005). National Climate Center (NCC, 1998) of China has further found that for winter and spring of more snow over the TP, the large-scale 500 hPa height pattern of '+ − +' meridional correlation mode prevails over East Asia in summer, which is characterized by significant positive correlation at high latitudes (in general, frequent development of blocking situation), negative correlation at mid-latitudes (low pressure disturbances frequently develop over the middle and lower basins of the Yangtze River) and significant positive correlation at lower latitudes (stronger subtropical high over the West Pacific with farther southern position than normal, i.e.…”
Section: Datasupporting
confidence: 90%
“…This implies that other external forcing factors can also exert an important effect on the inter-decadal variability of the summer precipitation in China. Among them, a special importance of the inter-decadal change in snow in the preceding winter and spring over the Tibetan Plateau (TP) has been stressed by numerous investigators in order to elucidate the interdecadal weakening of the Asian summer monsoon and variability of the summer precipitation in China (Li, 2002;Ding and Sun, 2003;Liu et al, 2003;Qian et al, 2003;Wu and Qian, 2003;Zhang et al, 2003Zhang et al, , 2004a. In contrast to the decreasing trend of the Eurasian winter and spring snow cover, especially from the mid-1970s, the winter and spring snow cover, snow depth and number of snow days over the TP have had an increasing trend during the last 45 years, with a significant increase occurring in the late 1970s.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, many studies based on modeling and observational data analysis have found a remarkable relationship between the winter or spring snow over the TP and rainfall over the mid-and lower-reaches of the Yangtze River Basin (YRB) in eastern China and South China in the subsequent summer (e.g. Wu and Qian, 2003;Qian et al, 2003;Zhang et al, 2004), primarily through two important effects of snow cover -influence on surface albedo and soil moisture (Barnett et al, 1989;Yasunari et al, 1991). Observational evidence indicates that the surface temperatures on the TP have increased by about 1.8 • C over the past 50 years (Wang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…First, through absorption and scattering, aerosols reduce downwelling insolation at the surface (dimming) (e.g., Ogren and Charlson, 1983;Qian et al, 2006), thus decreasing absorbed solar energy by snowpack. Second, absorbing particles (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…At the end of the 19th century, Blanford (1884) first revealed that the winter-spring snow in the Himalayas had a negative correlation with the succeeding summer monsoon rainfall over India. Thereafter, many researchers have proved using data analysis and numerical simulation that the Qinghai-Tibetan Plateau snow plays significant roles in climatic variations in Asia (Guo and Wang, 1986;Wei et al, 1998;Chen and Song, 2000;Qian et al, 2003;Zhang et al, 2012). The snow anomalies over the Qinghai-Tibetan Plateau change the soil moisture and the surface temperature through the snowmelt process at first, and subsequently alter heat, moisture, and radiation fluxes from the surface to the atmosphere.…”
Section: Introductionmentioning
confidence: 99%